Decoupling working memory impairment from grey matter volume changes in female patients with fibromyalgia: Moderating effect of depression - Ana Belén del Pino; Irene Peláez; Alejandro García-Romero; Maria Luisa Fernández-Sánchez; Paloma Barjola; Vanesa Soto-León; Antonio Oliviero; Francisco Mercado (NeuroImage)
Patients with fibromyalgia are characterised by having, along with persistent chronic pain, cognitive impairments, mainly in working memory capacity. It has been suggested that abnormalities in fronto-parietal neural circuits might account for this dysfunction. However, limited body of neuroimaging research and mixed or inconsistent results have led to inconclusive evidence. Our investigation aimed to explore the neural links between working memory dysfunction and brain grey matter volume in fibromyalgia using voxel-based morphometry (VBM), considering the influence of pain and affective symptoms. Thirty female patients with fibromyalgia and twenty-seven healthy female individuals participated in the present investigation. Working memory functioning was assessed using the Wechsler Adult Intelligence Scale III (WAIS-III) and the Wechsler Memory Scale III (WMS-III). VBM data (global and regional grey matter volume) were also analysed. As expected, fibromyalgia patients scored lower on Arithmetic, Letter-Number Sequencing and Working Memory Index than healthy individuals. Nonetheless, we found no differences in grey matter volume between groups. Moderation analyses highlighted the importance of considering affective symptoms of fibromyalgia, such as depression, to characterize associations between local grey matter volumes in the insula and prefrontal cortices (orbitofrontal and ventrolateral prefrontal cortex) with working memory functioning. These results suggest that moderate to severe symptoms of depression appear to be critical for understanding the emergence of associations between grey matter volume and working memory, offering valuable new insights into this complex relationship. Further research based on multimodal imaging approaches is needed to refine current findings and explore neural circuits underlying cognitive impairment in fibromyalgia.